B cell depletion or absence does not impede anti-tumor activity of PD-1 inhibitors. Issue 1 (14th June 2019) - Damsky, William; Jilaveanu, Lucia; Turner, Noel; Perry, Curtis; Zito, Christopher; Tomayko, Mary; Leventhal, Jonathan; Herold, Kevan; Meffre, Eric; Bosenberg, Marcus; Kluger, Harriet M.
Abstract : Background: PD-1 inhibitors are approved for multiple malignancies and function by stimulating T cells. However, the role of B cells in the anti-tumor activity of these drugs is unknown, as is their activity in patients who have received B cell depleting drugs or with immunoglobulin deficiencies. Methods: We studied B cell content in 40 melanomas from patients treated with pembrolizumab or nivolumab and assessed the association with response to therapy. Murine MC38 colon cancer and YUMMER1.7 melanoma models were used to determine whether concomitant anti-CD20 antibody injections diminish the anti-tumor effects of anti-PD-1. Results were validated in mu MT mice, which lack B cells. Results: B cells were sparse in most melanomas and B cell content was not associated with response to anti-PD-1 or overall survival. Employing MC38 and YUMMER1.7 models, we demonstrated that anti-CD20 antibodies reduce tumor-infiltrating B cells yet had no effect on tumor growth, response to PD-1 inhibition, or survival. In mu MT mice, T-cell dependent tumor rejection and anti-PD-1 responses were no different than in wildtype C57BL/6 J mice. Conclusions: The degree of tumor infiltrating B cell content is not associated with response to anti-PD-1 inhibitors in melanoma. PD-1 inhibitors cause tumor shrinkage in murine cancer models even when B cells are absent or are depleted. PD-1 inhibitors are likely to be active in patients with impaired B cell function, such as patients undergoing B cell depletion with drugs including rituximab for conditions such as B cell malignancies or autoimmune disorders.